Manejo de los materiales plásticos reciclados y mejoramiento de sus propiedades (INGE@UAN - TENDENCIAS EN LA INGENIERÍA, 2014)
This paper is a study of recycled plastic materials and its applications. It begins with a review of the concept of plastic, its properties and applications. In addition, we list the most commonly used plastic materials commercially available and those are being developed to reduce the impact on the environment. Also, a review of existing methodologies, mechanical and chemical, to process the recycled plastics to obtain parts, fuels or other plastics of this material is made. Finally, it is formulated an alternative for improving their quality.
Keywords: Recycled plastics; plastics materials